2015
DOI: 10.17140/droj-1-117
|View full text |Cite
|
Sign up to set email alerts
|

Association of Total and Differential White Blood Cell Counts to Development of Type 2 Diabetes in Mexican Americans in Cameron County Hispanic Cohort

Abstract: Objective To evaluate the relationship between total and differential White Blood Cell (WBC) counts with time to transition to type 2 diabetes in Mexican Americans using prospective data from the Cameron County Hispanic Cohort (CCHC). Results Multivariable Cox proportional hazards regression models revealed that obese Mexican-American cohort participants whose total WBC or granulocyte count increased over time had 1.39 and 1.35 times higher risk respectively of transition to type 2 diabetes when compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 35 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…WBC count increased with increase of BMI in BMI from 22 to 28, it was consistent with the previous studies which suggested that BMI had a significantly positive correlation with WBC counts. [16][17][18] When BMI was in 18 to 22, however, WBC count increased with the decreased of BMI. There was little evidence supporting the negative relationship between low BMI and WBC.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…WBC count increased with increase of BMI in BMI from 22 to 28, it was consistent with the previous studies which suggested that BMI had a significantly positive correlation with WBC counts. [16][17][18] When BMI was in 18 to 22, however, WBC count increased with the decreased of BMI. There was little evidence supporting the negative relationship between low BMI and WBC.…”
Section: Discussionmentioning
confidence: 97%
“…15 The association between BMI and WBC count was investigated. [16][17][18] Nagasawa et al found that WBC count had a positive correlation with BMI in a cross-sectional study of 3,594 Japanese (p = 0.001). 16 And similar results were in type 2 diabetes 17 , coronary, cancer and all-cause mortality 18 .…”
Section: Introductionmentioning
confidence: 98%
“…To demonstrate the importance of identifying interactions in epidemiologic studies, in this section we referred to an earlier finding from analyses of CCHC data with Cox proportional hazards regression model [ 8 ]. Briefly, using data from 636 participants in the CCHC, this study assessed crude and adjusted effects of total and differential WBC counts (lymphocytes, monocytes, and granulocytes), C-reactive protein (CRP), and Body Mass Index (BMI) in relation to time to progression to type 2 diabetes in Mexican Americans.…”
Section: Methodsmentioning
confidence: 99%
“…Our result indicated that family diabetes history and pre-diabetes status did not satisfy the proportional hazards assumption; hence all models that included these two variables were stratified by these variables by including strata statement in SAS Proc Phreg [ 18 ]. Details regarding the model development are described elsewhere [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation